Incidence, persistence, and clearance of anogenital human papillomavirus among men who have sex with men in Taiwan: a community cohort study - Zhou, Xinyi; Tian, Tian; Lu, Zhen; Yu, Yi-Fang; Li, Yuwei; Zhou, Yiguo; Lin, Yi-Fan; Strong, Carol; Zou, Huachun (Frontiers in Immunology, 2023)
Background Men who have sex with men (MSM) have an increased risk of human papillomavirus (HPV) infection. This study aimed to assess the incidence, persistence, and clearance of anogenital HPV infections among MSM and the correlates in a 3-year community cohort study. Methods From 2015 to 2019, MSM were recruited and followed up at 6, 12, 24, and 36 months in Taiwan. Questionnaires and anogenital swabs were collected at baseline and each follow-up visit. Thirty-seven HPV genotypes were tested and genotyped using the linear array HPV genotyping test. The incidence, persistence, and clearance rates of anogenital HPV infection and 95% confidence intervals (CIs) were estimated through Poisson regression. Correlates of the incidence and clearance rates were examined using a generalized estimating equations (GEE) model. Results A total of 201 MSM were retained in the cohort study with a median age of 27 years (interquartile range [IQR]: 24–32) at baseline. The incidence, persistence, and clearance rates of any anal HPV infection among MSM were 43.6 (95% CI: 33.7–55.6), 23.4 (17.7–30.2), and 58.3 (45.1–74.1) per 1,000 person months (pms), respectively. The incidence, persistence, and clearance rates of any penile HPV infection among MSM were 26.8 (20.1–34.9), 13.4 (8.0–20.9), and 51.5 (37.8–68.5) pms, respectively. MSM who did not consistently use a condom in receptive sex (adjusted odds ratio [AOR]: 2.06, 95% CIs: 1.14–3.72) were more likely to acquire any anal HPV infection. Age at recruitment (1.05, 1.01–1.09) was positively associated with any penile HPV incidence. MSM with over one sex partner in receptive anal sex (0.53, 0.30–0.94) were less likely to clear any anal HPV infection. MSM who were unemployed/students (0.55, 0.30–0.98) were less likely to clear any penile HPV infection. Conclusion High incidence and low clearance of anogenital HPV infection among MSM in the study serve as a reminder that this population needs to be targeted for HPV vaccination. It is essential for MSM to scale up HPV screening and adhere to safe sex.